Optimal Combination of Currency Assets and Algorithm Simulation under Exchange Rate Risk - Jun Wei (Complexity, 2020)
The excess money supply did not lead to a rapid rise in the price index, which in turn triggered inflation. In this case, the redetermination of the demand for money is particularly important. At the same time, with the continuous expansion of the capital market and the rapid development of the virtual economy, the virtual economy is gradually deviating from the real economy. When selecting assets, microentities often incorporate virtual economic assets into investment considerations. Therefore, it is necessary to establish a money demand model that considers the impact of virtual economic assets. This paper uses the asset selection of microentities as the microfoundation to establish a money demand model to explain its economic significance. And based on the money demand model established, a dynamic equilibrium model of the money market was established, and the stability of the dynamic equilibrium point of the money market was verified through mathematical deduction. Based on the dynamic equilibrium model of the money market, the impact of money supply was analyzed. In order to verify the correctness of the aforementioned theory, this paper conducts an empirical analysis. Through cointegration analysis and the vector error correction model (VECM model), the correctness and applicability of the established money demand model are verified, and money demand, total social wealth, spreads between expected stock returns and interest rates, and real estate expectations are found. There is a long-term equilibrium relationship between the rate of return and the interest rate. The total amount of social wealth, the expected rate of return on stocks, and the interest rate spread will have an impact on the demand for money in the short term.